Hubungan Tingkat Stres Dengan Siklus Menstruasi Pada Remaja Putri di SMAN 1 Wilayah Kerja Puskesmas Gedong Panjang Kota Sukabumi - Alipa Salsabilla; Susilawati Susilawati; Abdul Rahman La Ede (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescence is the time between childhood and adulthood when people start going through puberty. Menstruation is a sign of puberty in teenage girls. Menstrual disorders are among the reproductive health problems that teenage females are susceptible to during puberty. Adolescents are also more susceptible to stress because of changes in their bodies and minds as well as growing environmental pressures. Adolescent girls may experience menstrual cycle abnormalities as a result of this stress's disruption of the reproductive hormone balance. The objective of this study is to determine the relationship between stress levels and menstrual cycles among female adolescents at SMAN 1 in the service area of the Gedong Panjang Community Health Center, Sukabumi City. This research applied a correlational study design using a cross-sectional approach. The sample included 236 adolescent girls who were selected through proportional random sampling. Stress levels were assessed using the Perceived Stress Scale-10 (PSS-10) questionnaire, while menstrual cycle characteristics were evaluated using the Guttman scale. Data were analyzed using both univariate and bivariate methods, with the Chi-Square test applied at a significance level of α = 0.05, and the strength of the relationship was assessed using the contingency coefficient. According to the study's findings, 185 respondents (78,4%) reported moderate stress, while 190 respondents (80,5%) reported regular menstrual periods. With a contingency coefficient of 0.654 and a p-value of 0.000 0.05, the Chi-Square test results demonstrated a high correlation between stress levels and the menstrual cycle. There is a significant association and strong correlation between stress levels and the menstrual cycle, such that increased stress levels may potentially increase the risk of menstrual disorders among adolescent girls at SMAN 1 within the service area of the Gedong Panjang Community Health Center in Sukabumi City. Keywords: Adolescent Girls, Menstrual Cycle, Stress Level. ABSTRAK Masa remaja merupakan periode peralihan dari masa anak menuju dewasa, di mana individu mulai mengalami pubertas. Pada remaja perempuan, pubertas ditandai dengan terjadinya menstruasi. Pada masa pubertas, remaja putri berpotensi mengalami berbagai permasalahan kesehatan reproduksi, salah satunya gangguan menstruasi. Selain itu, remaja juga rentan mengalami stres akibat perubahan fisik, psikologis, serta tuntutan lingkungan yang semakin meningkat. Kondisi stres tersebut dapat memengaruhi keseimbangan hormon reproduksi sehingga berpotensi menyebabkan gangguan siklus menstruasi pada remaja putri. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana tingkat stres dan siklus menstruasi remaja putri di SMAN 1 di wilayah kerja Puskesmas Gedong Panjang Kota Sukabumi berhubungan. Penelitian ini menggunakan desain korelasional dengan pendekatan cross-sectional.Sampel penelitian berjumlah 236 remaja putri Sampel penelitian dipilih menggunakan teknik proportional random sampling. Pengukuran tingkat stres dilakukan dengan menggunakan kuesioner Perceived Stress Scale-10 (PSS-10), sedangkan siklus menstruasi diukur menggunakan skala Guttman. Analisis data dilakukan melalui analisis univariat dan bivariat dengan uji Chi-Square pada tingkat signifikansi α = 0,05 dan menilai keeratan hubungan dengan koefisien kontengensi. Berdasarkan temuan studi ini, 185 responden (78,4%) melaporkan mengalami tingkat stres sedang, sementara 190 responden (80,5%) melaporkan siklus menstruasi yang teratur. Dengan koefisien kontingensi sebesar 0,654 dan nilai p sebesar 0,000 0,05, hasil uji Chi-Square menunjukkan adanya korelasi yang kuat antara tingkat stres dan siklus menstruasi. Terdapat korelasi hubungan yang signifikan dengan keterikatan hubungan yang kuat antara tingkat stres dan siklus menstruasi, di mana peningkatan tingkat stres berpotensi meningkatkan risiko gangguan menstruasi pada remaja putri di SMAN 1 wilayah kerja Puskesmas Gedong Panjang Kota Sukabumi. Kata Kunci: Remaja Putri, Siklus Menstruasi, Tingkat Stres.